Modulated Thermoelectric Properties of Organic Semiconductors Using Field‐Effect Transistors. (7th April 2015) - Zhang, Fengjiao; Zang, Yaping; Huang, Dazhen; Di, Chong‐an; Gao, Xike; Sirringhaus, Henning; Zhu, Daoben
Abstract : Organic thermoelectric materials, which can transform heat flow into electricity, have great potential for flexible, ultra‐low‐cost and large‐area thermoelectric applications. Despite rapid developments of organic thermoelectric materials, exploration and investigation of promising organic thermoelectric semiconductors still remain as a challenge. Here, the thermoelectric properties of several p‐ and n‐type organic semiconductors are investigated and studied, in particular, how the electric field modulations of the Seebeck coefficient in organic field‐effect transistors (OFETs) compare with the Seebeck coefficient in chemically doped films. The extracted relationship between the Seebeck coefficient ( S ) and electrical conductivity ( σ ) from the field‐effect transistor (FET) geometry is in good agreement with that of chemically doped films, enabling the investigation of the trade‐off relationship among σ, S, carrier concentration, and charging level. The results make OFETs an effective candidate for the thermoelectric studies of organic semiconductors. Abstract : Investigation of thermoelectric properties of organic semiconductors is a fundamental issue toward effective application of high‐performance organic thermoelectric materials. It is reported on a systematic study of the thermoelectric properties for organic semiconductors via field‐effect transistors, which indicates that organic transistors should provide an effective platform to accelerate the screening of promising organic thermoelectric materials.